2006
DOI: 10.1265/ehpm.11.136
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and myelotoxic effects of single administration of 2,3,7,8-tetrabromodibenzo-p-dioxin in rats

Abstract: Objective: Systemic and myelotoxic effects of 2,3,7,8-tetrabromodibenzo-p-dioxin (TBDD) were examined by the single administration of TBDD by gavage to rats.Methods: Fifteen Wistar rats of both sexes per group received 0, 10, 30, 100 or 300 μg TBDD/kg body weight. Rats surviving to the scheduled necropsy on Days 2, 7 and 36 after TBDD administration were examined for growth rate, organ weight, hematology, histopathology and adipose tissue levels of TBDD.Results: Three 300 μg/kg-dosed females died on Days 21, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
4
7
0
Order By: Relevance
“…This finding might extend the previously reported findings 11,14,15,37) of the enhanced TBDD hepatotoxicity of female rats to higher susceptibility of female rats to the formation of GST-P-positive liver foci than males. Lucier et al 38) demonstrated using the two-stage hepatocarcinogenesis model that the number of GST-P-positive foci were greater in intact female rats receiving a single ip injection of DEN followed by repeated oral administration of TCDD at a dose equivalent to 100 ng/kg/d for 30 wk than in ovariectomized rats receiving DEN and TCDD.…”
Section: Days After Administrationsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding might extend the previously reported findings 11,14,15,37) of the enhanced TBDD hepatotoxicity of female rats to higher susceptibility of female rats to the formation of GST-P-positive liver foci than males. Lucier et al 38) demonstrated using the two-stage hepatocarcinogenesis model that the number of GST-P-positive foci were greater in intact female rats receiving a single ip injection of DEN followed by repeated oral administration of TCDD at a dose equivalent to 100 ng/kg/d for 30 wk than in ovariectomized rats receiving DEN and TCDD.…”
Section: Days After Administrationsupporting
confidence: 90%
“…The animals were quarantined and acclimated for 2 wk, and then divided by stratified randomization into 5 body weight-matched groups, each comprising 15 rats of both sexes. The conditions under which the animals were raised were described in detail previously 14,15) . The animals were cared for according to the Guide for the Care and Use of Laboratory Animals 34) .…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single oral and intraperitoneal administrations of TBDD were reported to induce teratogenic effects in mice (Birnbaum et al, 1991) and to induce thymic atrophy, body weight loss and induction of hepatic microsomal enzymes in immature male rats (Mason et al, 1987). Yamamoto et al (2006) demonstrated that a single administration of TBDD by gavage to rats induced systemic and myelotoxic effects associated with a wasting syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of TBDD has been reported to be less potent than that of 2,3,7,8-tetrachlorodibenzo-pdioxin (TCDD) (Ivens et al, 1992 andBirnbaum et al, 1991;Yamamoto et al, 2006). TCDD is known to target the liver in humans and experimental animals (IARC, 1997;Gupta et al, 1973;Jones and Butler, 1974;Kociba et al, 1976;Plüss et al, 1988;Pohjanvirta et al, 1989).…”
Section: Introductionmentioning
confidence: 99%